Digital Marketing and Global Marketing - Kusdiyanto; Saputro, Edy Purwo; Mabruroh; Setyaningrum, Dewi Probowati (Urecol Journal. Part F: Community Development, 2023)
Global marketing and digital marketing are key in entering the competitive global market. Therefore, competitive advantage is important even though on the other hand it cannot ignore the role of comparative advantage. Related to this, the millennial generation has an interest in knowing, understanding and mapping strategies to enter the global market with digital marketing. The method used was education and literacy involving 20 millennials. Tutorials with slides are expected to increase understanding of global markets and digital marketing. The results show that there is a collective awareness of the importance of understanding global markets and digital marketing to be able to win the competition in the era of globalization.